Psikoedukasi “Remaja Berani, Tolak Sentuhan Tidak Pantas” Sebagai Upaya Preventif Pelecehan Seksual di SMA Negeri 9 Bulukumba - Irmayanti Irmayanti; Khalisah Humairah; Salsabila Rahman; Irdianti Irdianti (Universitas Negeri Makassar, 2025)
The psychoeducation activity was conducted at UPT SMAN 9 Bulukumba with the aim of increasing adolescents’ understanding of sexual violence, especially related to inappropriate touching. The main objective was to serve as a preventive measure so that teenagers could protect themselves early on. The psychoeducation program titled